Small ruminant production in Malawi - Chimbaza, T.L. (1986)
The paper reports on small ruminant production in Malawi. It discusses on exports and imports of products, marketing channels and value of marketing products, local consumption, demand and systems of production included. Italso reviews small ruminant research in Malawi and summarises current and future research development priorities.